Comparative performance of rearward and forward-facing child restraint systems with common use errors: Effect on crash injury risk for a 1-year-old occupant. (17th February 2022) - Whyte, Tom; Kent, Nicholas; Bilston, Lynne E.; Brown, Julie
Abstract: Objective: To compare how errors in child restraint use influence crash injury risk in rearward and forward-facing restraints for a 1-year old occupant. Methods: Three convertible child restraint systems (CRS) were subjected to frontal dynamic sled tests at 56 km/h in rearward-facing and forward-facing modes in a correct use (baseline) condition and in five incorrect use conditions: loose securing belt, loose harness, partial harness use, top tether slack, and three minor errors. Excursion, head, and chest 3 ms resultant acceleration, HIC15, and neck forces and moments of a Q1 anthropomorphic test device (ATD) seated in the restraints were measured. The effect of incorrect use on each outcome and restraint type was analyzed. Results: The influence of errors varied across different outcome variables, the three restraints tested and orientation modes. Excursion increased in four of five incorrect use conditions in both rearward and forward-facing orientations. A very loose harness increased four of five outcome variables in at least one forward-facing restraint, whereas only excursion was increased when rearward-facing. Overall, there tended to be a more negative effect of incorrect use (demonstrated through increases in outcome variables compared to the baseline) in the forward-facing orientation. Conclusions: Overall, errors in use tended to have a larger negative impact on forward-facing restraints than rearward-facing restraints. Given the widespread nature of errors in use, this adds further weight to arguments to keep children rearward-facing to 12 months of age and older. The results also highlight a variation in response to errors across differently designed restraints, suggesting the influence of errors may be minimized by restraint design that is more resistant to errors.